CORPORATE CULTURE AS AN OBJECT OF ORGANIZATIONAL CHANGE - Ізюмцева, Наталія; Подопригора, Аліна (Socio-economic relations in the digital society, 2020)
Currently, companies around the world are faced with the fact that the market is becoming increasingly unstable, and the demands of shareholders and customers are growing Most organizations are aware of the need for change to improve their performance and improve product quality. At the same time, the human factor directly related to the implementation of these decisions is often ignored. Change is an ongoing process. If business leaders want to take the lead in the market today, they must learn to adequately respond to the ever changing number of market changes. Managers should analyze the existing structure of their companies, the general business policy, the ability to use new technologies and their relationships with staff and customers. Most organizations are concerned about the need for changes in order to improve the performance of the company and the quality of its products, but the human factor directly related to the implementation of these decisions is often ignored. For successful implementation of global changes, companies need to establish a relationship between the organization, the employee and the changes made. This is achieved by encouraging more flexible relationships within the organization’s staff. Changes are inconvenient and difficult to adjust. But at the same time, changes are vital they determine life itself. The main thing is to learn to accept changes, both professionally and personally. Changes in corporate culture occur regardless of our desire. Corporate culture consists of cultural substances represented by different people from other groups. Therefore, the company should be able to diagnose its own culture, constantly answering questions: what kind of people are involved in the organization, what is their behavior and ways of communicating in a team, what values are they guided by, what rules are the basis of their professional relations, where there is a framework of leadership style.